The Quantified Self and Digital Piety: Analyzing Islamic Prayer Apps, Datafication, and their Impact on Daily Worship - Nandar Hlaing; Aung Myint; Murat Arslan (Yayasan Adra Karima Hubbi, 2026)
The widespread adoption of Islamic prayer applications has introduced new forms of digital piety in which acts of worship become increasingly structured, quantified, and mediated through mobile technologies. The rise of these apps reflects broader cultural shifts toward datafication, self-tracking, and algorithmically guided religious practice. While prayer apps offer convenience, reminders, and personalized worship analytics, concerns have emerged regarding overreliance on digital tools, potential erosion of spiritual intentionality, and the implications of data extraction for user privacy. These dynamics highlight the need to critically examine how quantified self technologies shape Muslim devotional life. This study aims to analyze the influence of Islamic prayer apps on daily worship by investigating how datafication, algorithmic nudges, and quantified worship metrics affect users’ spiritual habits and perceptions of religious discipline. The research seeks to explore both the empowering and constraining effects of digital piety on contemporary Muslim practice. A mixed-methods approach was employed, combining a quantitative survey of 268 Muslim prayer app users with qualitative interviews involving twenty participants who regularly engage with worship-tracking features. Document analysis of popular prayer apps was also conducted to examine interface design, tracking mechanisms, and data-collection practices. Findings reveal that prayer apps significantly increase worship consistency, particularly in maintaining prayer schedules and tracking missed prayers. However, the quantification of worship introduces psychological dependence on reminders and metrics, shifting spiritual motivation from intrinsic intentionality to external digital cues. The study concludes that while prayer apps enhance ritual discipline, they also reshape devotional experiences through datafication, necessitating ethical reflection on privacy, autonomy, and the meaning of worship in a digital age.